Faktor – Faktor Yang Mempengaruhi Kepuasan Kerja Personel Pada Unit (Pengendalian Massa) Dalmas Direktorat Samapta Polda Kaltim - Saputri, Niken; Hasan, Syahril; Yulianti, Tutik (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Balikpapan, 2026)
The Community Control Unit (Unit Pengendalian Masyarakat/Dalmas) of the East Kalimantan Police Samapta Directorate often has to face demonstrations that lead to chaos in carrying out its duties. The role of maintaining social order during demonstrations results in psychological pressure for police officers, which can lead to low levels of work satisfaction. This study aims to examine the factors (leadership, work stress, and work environment) that influence the work satisfaction of police personnel. This study used a quantitative survey method of 190 personnel in the Dalmas unit of the Samapta Directorate of East Kalimantan Police. The research found that leadership and work environment variables did not have a significant influence on work satisfaction in the Dalmas unit of the Directorate of Samapta Polda East Kalimantan. Meanwhile, the work stress variable has a negative and significant influence on work satisfaction in the Dalmas unit of the Directorate of Samapta Polda East Kalimantan, so that the higher the work stress, the lower the work satisfaction. And vice versa. These findings prompted the Dalmas leadership of the East Kalimantan Police Samapta Directorate to pay more attention to the psychological condition of police personnel. This is because work-related stress and pressures in carrying out work not only have an impact on work satisfaction, but can interfere with work performance.